Metal monatomic electrocatalyst as well as preparation method and application thereof
By using the anchoring and weak reduction of zero-dimensional carbon dots, uniform loading and dispersion of metal single atoms is achieved, and the problems of cumbersome synthesis steps and low loading are solved, and efficient and low-cost preparation of metal single atom electrocatalysts are achieved.
Patent Information
- Application Number
- CN202510405148.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The synthesis steps of traditional metal single-atom electrocatalysts are complicated, the load of metal single-atoms is low, and the limitations on metal types are large, making it difficult to mass production, which seriously restricts its large-scale application.
By using zero-dimensional carbon dots as a carrier, the anchoring and weak reduction of carbon dots can achieve uniform loading and dispersion of metal single atoms. The method includes stirring and sonication under the mixture of carbon dot solution and carbon black suspension, followed by dropping the metal precursor solution for impregnation and adsorption at room temperature, and finally drying at low temperature to obtain a metal single-atom electrocatalyst.
It has achieved the preparation of single-atom electrocatalysts with high metal load, with good dispersion, simple preparation process, simple operation and low energy consumption. It is suitable for the preparation of various types of metal single-atom electrocatalysts, greatly reducing production costs.
Smart Images

Figure CN119920919A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a metal single-atom electrocatalyst and a preparation method and application thereof. Background Art
[0002] The problems of excessive consumption of fossil energy and environmental pollution are becoming increasingly serious. The development of new energy technologies is one of the important ways to solve current energy and environmental problems, such as the development of methanol fuel cells and hydrogen fuel cells that can directly convert chemical energy into electrical energy.
[0003] Shrinking metal nanoparticles or clusters to atomic scale can not only effectively reduce the cost of catalysts (especially precious metals), but also provide uniform active sites. Therefore, metal single-atom catalysts have received widespread attention in recent years. Compared with metal cluster catalysts and alloy catalysts, metal single-atom catalysts are increasingly widely used in new energy technologies including methanol fuel cells due to their high catalytic activity, adjustable coordination environment and high atomic utilization efficiency. Therefore, the development of efficient metal single-atom electrocatalysts and matching batch synthesis technologies is of great significance to promote the rapid development of many new energy technologies. However, the synthesis steps of metal single-atom electrocatalysts usually have cumbersome and complicated steps, low metal single-atom loading, and large restrictions on metal types, which makes it difficult to mass-produce metal single-atom electrocatalysts, seriously restricting their large-scale application.
[0004] The metal atoms in metal single-atom catalysts need to be highly dispersed on a suitable carrier, and the sharp increase in specific surface area will lead to a significant increase in the free energy of the metal surface, making it easy for isolated metal atoms to agglomerate and form clusters during the preparation and reaction process, thereby reducing the active sites and reducing the catalytic efficiency and stability of the methanol oxidation reaction. One of the effective ways to solve this problem is to use suitable carrier materials to provide abundant anchoring sites for single atoms to prevent them from agglomerating. Carbon dots (CDs), as a zero-dimensional carbon nanomaterial with significant fluorescence properties, exhibit excellent performance in the fields of light and electrochemistry due to their low cost, easy accessibility, unique electron transport ability and large specific surface area. The surface of carbon dots contains abundant functional groups, such as oxygen-containing functional groups such as carboxyl (-COOH) and hydroxyl (-OH), as well as heteroatom functional groups brought by non-metallic doping of nitrogen, boron, phosphorus and fluorine. The above functional groups have strong binding effects on most types of metals. On the one hand, they can provide abundant binding sites for anchoring and stabilizing isolated metal atoms, thereby increasing the metal loading; on the other hand, they have a regulating effect on the structure and electron distribution of the carbon dots themselves. It also has a significant impact on the electronic state and structure of metal catalysts. These heteroatom functional groups even have the function of providing electrons, which makes the carbon dots have a certain reduction ability. No additional high-temperature calcination, chemical reduction and other treatment steps are required. Metal single-atom catalysts can be obtained by simple room-temperature immersion adsorption.
[0005] Chinese patent application 202210817899.0 discloses a nitrogen-containing carbon quantum dot-modified platinum-ruthenium bimetallic methanol oxidation electrocatalyst and its preparation method. The specific content includes that the platinum-ruthenium bimetallic alloy cluster electrocatalyst is obtained by reducing the metal salt with a strong reducing agent sodium borohydride and loading it on carbon black with the assistance of nitrogen-containing carbon dots, and the distribution form of the metal on the carbon black is a cluster particle form; the disclosure utilizes the surface functional groups of nitrogen-containing carbon dots to anchor the platinum-ruthenium metal, so that the platinum-ruthenium agglomerates are fully dispersed and the catalytic activity is improved. However, the patent does not involve a method for preparing a metal single-atom catalyst, let alone that the weak reducibility of carbon dots to metals helps the formation of metal single atoms.
[0006] Chinese patent application 202310173076.3 discloses a method for synthesizing an ultra-high dispersed platinum-copper methanol oxidation electrocatalyst. The specific content includes that the platinum-copper bimetallic alloy cluster electrocatalyst is obtained by reducing the metal salt with a strong reducing agent sodium borohydride and loading it on carbon black with the assistance of nitrogen-phosphorus-carbon dots, and the distribution form of the metal on the carbon black is a cluster particle form; the disclosure utilizes the functional groups of nitrogen-phosphorus-carbon dots to anchor the platinum-copper metals, and utilizes the structural regulating effect of carbon dots on platinum and copper to improve the electrocatalytic activity. However, the patent does not involve a method for preparing a metal single atom catalyst, let alone the influence of the distribution form of metal single atoms on methanol oxidation.
[0007] Jiahui Liang et al. disclosed in the article "Boosting the Methanol Oxidation Reaction Activity of Pt-Ru Clusters via Resonance Energy Transfer" (Small 19 (2023) 202302149) a method for enhancing the methanol oxidation reaction activity of a platinum-ruthenium cluster catalyst by using resonance energy transfer. The specific content includes that the platinum-ruthenium bimetallic alloy cluster electrocatalyst reduces the metal salt by the strong reducing agent sodium borohydride, and the clusters are formed and loaded on carbon black with the assistance of resonance energy transfer between nitrogen-containing carbon dots and platinum; the disclosure discovers that there is resonance energy transfer between carbon dots and metals through the fluorescence quenching effect between carbon dots and platinum and ruthenium, and changes the electronic structure of the metal, reduces the d-band center of platinum, and improves the catalytic activity of the metal catalyst. However, the document does not disclose a method for preparing a metal single atom catalyst, nor does it disclose that the weak reducibility of carbon dots to metals contributes to the formation of metal single atoms.
[0008] In view of the above-mentioned technical phenomena, how to synthesize metal single-atom electrocatalysts through carbon dots is of great significance to promoting the large-scale production of metal single-atom electrocatalysts and the rapid development of related new energy technology fields. Summary of the invention
[0009] The purpose of the present invention is to provide a metal single-atom electrocatalyst and its preparation method and application, so as to solve the technical problems of traditional metal single-atom electrocatalysts such as complicated preparation process, low metal loading, limited types and high cost.
[0010] On the one hand, the present invention provides a metal single-atom electrocatalyst, which adopts the following technical solution: A metal single-atom electrocatalyst comprising a carrier and an active center, The carrier is a zero-dimensional carbon dot; The active center is a metal dispersed in the form of a single atom, and the metal is loaded on a zero-dimensional carbon point.
[0011] On the other hand, the present application also provides a method for preparing a metal single-atom electrocatalyst, comprising the following steps: S1, dissolving a nitrogen source and citric acid in deionized water, mixing them evenly and placing them in a reactor, cooling and filtering after the reaction is completed to obtain a nitrogen-doped carbon dot solution; S2, taking conductive carbon black and placing it in deionized water, and ultrasonically treating it for 1-2 hours to obtain a carbon black suspension; S3, mixing the nitrogen-doped carbon dot solution obtained in step S1 and the carbon black suspension obtained in step S2, stirring for 48 hours, filtering, and obtaining carbon black adsorbed with carbon dots on filter paper; S4. Use ultrasound to place the carbon black adsorbed on the filter paper in step S3 in deionized water to obtain a mixed solution, and drop the metal precursor solution into the mixed solution, stir, and immerse and adsorb at room temperature for 24 hours, filter to obtain a filter residue, and dry the filter residue at 50-60°C to obtain a metal single-atom electrocatalyst.
[0012] Preferably, the nitrogen source in step S1 is any one of urea and ethylenediamine.
[0013] Preferably, in step S1, the reaction temperature of the reactor is set to 160-240° C., and the reaction time is 8-12 h.
[0014] Preferably, in step S1, 50-100 mg of nitrogen source is dissolved in each milliliter of deionized water; In the step S1, 25-50 mg of citric acid is dissolved in each milliliter of deionized water.
[0015] In the step S2, 0.6-0.8 mg of conductive carbon black is dissolved per milliliter of deionized water.
[0016] Preferably, in step S3, the volume ratio of the nitrogen-doped carbon dot solution to the carbon black suspension is (0.09-0.2):1.
[0017] Preferably, the metal in the metal precursor solution in step S4 includes any one or more of ruthenium, rhodium, palladium, osmium, iridium, platinum, rhenium, manganese, iron, cobalt, nickel, and zinc.
[0018] Preferably, the metal precursor in the metal precursor solution in step S4 includes one or more of ruthenium chloride, chlororhodic acid, chloropalladic acid, chloroosmic acid, chloroiridic acid, chloroplatinic acid, rhenium chloride, manganese sulfate, manganese chloride, manganese nitrate, ferric sulfate, ferric chloride, ferric nitrate, cobalt sulfate, cobalt chloride, cobalt nitrate, nickel sulfate, nickel chloride, nickel nitrate, zinc sulfate, zinc chloride, and zinc nitrate.
[0019] Preferably, the concentration of the metal precursor solution in step S4 is 0.0025 mol / L; The metal precursor solution in step S4 is added at a rate of 0.1-10 mL / min; In the step S4, the volume ratio of the mixed solution to the metal precursor solution is 4:(1-1.5).
[0020] On the other hand, the present invention also provides the use of the above-mentioned metal single-atom electrocatalyst in an electrocatalytic reaction.
[0021] In summary, the present invention includes the following beneficial technical effects: 1. The metal single-atom electrocatalyst provided by the present invention has good dispersion by the anchoring and reduction effect of carbon dots, and the metal single atoms are uniformly loaded on the zero-dimensional carbon dots. The rich heteroatom functional groups provide a large number of anchor points for the single atoms, thereby preparing single-atom electrocatalysts with high metal loading. In addition, compared with other preparation methods of metal single-atom electrocatalysts such as atomic layer deposition and high-temperature pyrolysis, the preparation method of the metal single-atom electrocatalyst has the advantages of simple preparation process, easy operation and low energy consumption. Metal single-atom electrocatalysts with high metal single-atom loading and uniform dispersion can be prepared by a simple room-temperature impregnation method, which is convenient for batch synthesis on an industrial scale and greatly reduces the production cost of metal single-atom electrocatalysts.
[0022] 2. The preparation method of the metal single-atom electrocatalyst provided by the present invention is applicable to the preparation of various types of metal single-atom electrocatalysts, including precious metal-based and non-precious metal-based single-atom electrocatalysts. At the same time, it can prepare multi-metal synergistic single-atom electrocatalysts and has excellent universality.
[0023] 3. The present invention analyzes the Pt L-edge X-ray absorption near-edge structure spectrum of Ni, Pt-NCDs / C single-atom catalysts, showing that the coordination environment around the platinum atoms is mainly platinum-chlorine coordination and platinum-nitrogen coordination, and the crystal plane parameters corresponding to nickel and platinum metals do not appear in the X-ray diffraction pattern, which explains the formation and high dispersion of nickel and platinum single atoms; and by analyzing the spherical aberration electron microscopy images of Co, Pd, Pt-NCDs / C single-atom catalysts, the formation of cobalt, palladium, and platinum metal single atoms is proved.
[0024] 4. A fuel cell is a chemical device that directly converts the chemical energy of a fuel into electrical energy, also known as an electrochemical generator. Since a fuel cell converts the Gibbs free energy portion of the chemical energy of a fuel into electrical energy through an electrochemical reaction, it is not limited by the Carnot cycle effect and is therefore highly efficient. In addition, a fuel cell uses fuel and oxygen as raw materials and has no mechanical transmission components, so it emits very little harmful gas and has a long service life. This application uses a classic three-electrode system to test the electrochemical methanol oxidation catalytic performance of a Pt-NCDs / C single atom catalyst in an alkaline medium (1 mol / L KOH+1 mol / L CH3OH), and the optimal mass activity reaches 6611.73 mA / mg Pt . BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the Fourier infrared spectrum of the Pt-NCDs / C single atom catalyst and carbon dots prepared in Example 1 of the present invention.
[0026] Figure 2It is a mass activity diagram of electrochemical methanol oxidation of the Pt-NCDs / C single atom catalyst prepared in Example 1 of the present invention, the Pt-NCDs / C-Cluster cluster catalyst prepared in Comparative Example 1, and a commercial platinum-carbon catalyst.
[0027] Figure 3 It is an it (chronoamperometric) curve diagram of the Pt-NCDs / C single atom catalyst prepared in Example 1 of the present invention, the Pt-NCDs / C-Cluster cluster catalyst prepared in Comparative Example 1, and a commercial platinum-carbon catalyst.
[0028] Figure 4 These are X-ray diffraction patterns of the Pt-NCDs / C single atom catalyst prepared in Example 1 of the present invention, the Pd-NCDs / C single atom catalyst prepared in Example 2, the Zn-NCDs / C single atom catalyst prepared in Example 3, the Ni, Pt-NCDs / C single atom catalyst prepared in Example 4, the Co, Pd, Pt-NCDs / C single atom catalyst prepared in Example 5, the Pt-NCDs / C-Cluster cluster catalyst prepared in Comparative Example 1, the Pd, Ru-NCDs / C-Cluster cluster catalyst prepared in Comparative Example 2, as well as conductive carbon black and commercial palladium-carbon catalyst.
[0029] Figure 5 This is the Pt L-edge X-ray absorption near-edge structure spectrum of the Ni, Pt-NCDs / C single-atom catalyst prepared in Example 4 of the present invention.
[0030] Figure 6 This is a spherical aberration electron microscope image of the Co, Pd, Pt-NCDs / C single atom catalyst prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0031] The following is combined with Examples 1-5, Comparative Examples 1-2 and Attached Figure 1-6 The present invention is described in further detail.
[0032] Example 1 A method for preparing a metal single-atom electrocatalyst, wherein metal platinum is loaded on a zero-dimensional carbon dot in the form of a single atom, and the specific preparation method is as follows: S1. Take 2 g of urea and 0.5 g of citric acid and dissolve them in 20 mL of deionized water. Mix them evenly and place them in a polytetrafluoroethylene reactor. Set the reaction temperature of the polytetrafluoroethylene reactor to 200 °C and the reaction time to 12 h. After the reaction is completed, cool the obtained product to room temperature and filter it to remove insoluble impurities to obtain an orange-yellow nitrogen-doped carbon dot solution. S2, take 30 mg of conductive carbon black BP20000, add it into 50 mL of deionized water, and treat it ultrasonically for 1.5 h to obtain a carbon black suspension; S3, taking the carbon black suspension prepared in step S2 and mixing it with 4.5 mL of the nitrogen-doped carbon dot solution prepared in step S1, stirring at room temperature for 48 h, filtering, and obtaining carbon black adsorbed with carbon dots on filter paper; S4. Using ultrasound, the carbon black adsorbed with carbon dots on the filter paper in step S3 is placed in 40 mL of deionized water to obtain a mixed solution, and 10 mL of 0.0025 mol / L chloroplatinic acid solution is added dropwise to the mixed solution at a dropping rate of 0.15 mL / min. The mixture is stirred at room temperature for 24 h, filtered to obtain a filter residue, and dried in a constant temperature oven set at 50° C. to obtain a Pt-NCDs / C single atom catalyst loaded with platinum single atoms.
[0033] The inductively coupled plasma atomic emission spectrometry determined that the Pt atom ratio in the Pt-NCDs / C single atom catalyst prepared in Example 1 was 5.6%.
[0034] Reference Figure 1 , Figure 1 The Fourier transform infrared spectra of the Pt-NCDs / C single atom catalyst and carbon dots prepared in Example 1 are shown at 550 cm -1 At 3190 cm, a strong signal related to N-Pt stretching vibration appeared in the Pt-NCDs / C single atom catalyst, while the carbon dots showed a strong signal at 3190 cm -1 The initial stretching vibration absorption peak of NH at 40° disappeared, proving that the heteroatom functional groups (amino groups) in the carbon dots are the binding sites for Pt.
[0035] Reference Figure 2 , Figure 2 The mass activity diagram of the electrochemical methanol oxidation of the Pt-NCDs / C single atom catalyst prepared in Example 1 and the commercial platinum carbon catalyst. A fuel cell is a chemical device that directly converts the chemical energy of a fuel into electrical energy, also known as an electrochemical generator. It is the fourth power generation technology after hydroelectric power generation, thermal power generation and atomic power generation. Since the fuel cell converts the Gibbs free energy part of the chemical energy of the fuel into electrical energy through an electrochemical reaction, it is not limited by the Carnot cycle effect, so it is highly efficient; in addition, the fuel cell uses fuel and oxygen as raw materials, and has no mechanical transmission parts, so the emission of harmful gases is very small and the service life is long. From the perspective of energy conservation and ecological environment protection, fuel cells are the most promising power generation technology. The Pt-NCDs / C single atom catalyst prepared in Example 1 and the commercial platinum carbon catalyst were tested for electrochemical methanol oxidation catalytic performance in an alkaline medium (1 mol / L KOH+1 mol / L CH3OH) using a classic three-electrode system. It can be seen that the mass activity of the commercial platinum carbon catalyst is 1363.11 mA / mg PtThe mass activity of the Pt-NCDs / C single atom catalyst obtained in this example is 6611.73 mA / mg Pt , which is 4.85 times that of commercial platinum-carbon catalyst.
[0036] Reference Figure 3 , Figure 3 The it (chronoamperometry) curves of the Pt-NCDs / C single atom catalyst and the commercial platinum carbon catalyst prepared in Example 1 are shown. The electrochemical stability test of the Pt-NCDs / C single atom catalyst and the commercial platinum carbon catalyst prepared in Example 1 was carried out in an alkaline medium (1 mol / L KOH+1 mol / L CH3OH). After 5000 s of constant voltage operation, the current density of the Pt-NCDs / C single atom catalyst was higher than that of the commercial platinum carbon catalyst, indicating that the Pt-NCDs / C single atom catalyst has better stability.
[0037] Reference Figure 4 , Figure 4 The X-ray diffraction patterns of the Pt-NCDs / C single atom catalyst prepared in Example 1, conductive carbon black and commercial palladium carbon catalyst are shown. The peak shape of the Pt-NCDs / C single atom catalyst is similar to that of the conductive carbon black, and the crystal plane parameters corresponding to platinum metal do not appear, indicating the formation and high dispersion of platinum single atoms.
[0038] Example 2 A method for preparing a metal single-atom electrocatalyst, wherein metal palladium is loaded on a zero-dimensional carbon dot in the form of a single atom, and the specific preparation method is as follows: S1. Dissolve 2 g of urea and 1 g of citric acid in 20 mL of deionized water, mix well and place in a polytetrafluoroethylene reactor. Set the reaction temperature of the polytetrafluoroethylene reactor to 220 °C and the reaction time to 8 h. After the reaction is completed, cool the obtained product to room temperature and filter to remove insoluble impurities to obtain an orange-red nitrogen-doped carbon dot solution. S2, take 30 mg of conductive carbon black BP2000 and add it into 50 mL of deionized water, and treat it by ultrasound for 1 h to obtain a carbon black suspension; S3, taking the carbon black suspension prepared in step S2 and mixing it with 6 mL of the nitrogen-doped carbon dot solution prepared in step S1, stirring at room temperature for 48 h, filtering, and obtaining carbon black adsorbed with carbon dots on filter paper; S4. Using ultrasound, the carbon black adsorbed with carbon dots on the filter paper in step S3 is placed in 40 mL of deionized water to obtain a mixed solution, and 10 mL of 0.0025 mol / L palladium chloride solution is added dropwise to the mixed solution at a dropping rate of 0.1 mL / min. The mixture is stirred at room temperature for 24 h, filtered to obtain a filter residue, and dried in a constant temperature oven set at 50° C. to obtain a Pd-NCDs / C single atom catalyst loaded with palladium single atoms.
[0039] Reference Figure 4 , Figure 4 The X-ray diffraction patterns of the Pd-NCDs / C single atom catalyst prepared in Example 2, as well as conductive carbon black and commercial palladium carbon catalyst, show that the peak shape of the Pd-NCDs / C single atom catalyst is similar to that of the conductive carbon black, and the crystal plane parameters corresponding to palladium metal do not appear, indicating the formation and high dispersion of palladium single atoms.
[0040] Example 3 A method for preparing a metal single-atom electrocatalyst, wherein metal zinc is loaded on a zero-dimensional carbon dot in the form of a single atom. The specific preparation method is as follows: S1. Dissolve 1 g of ethylenediamine and 1 g of citric acid in 20 mL of deionized water, mix well and place in a polytetrafluoroethylene reactor. Set the reaction temperature of the polytetrafluoroethylene reactor to 180°C and the reaction time to 12 h. After the reaction is completed, cool the obtained product to room temperature and filter to remove insoluble impurities to obtain a reddish-brown nitrogen-doped carbon dot solution. S2, take 40 mg of conductive carbon black BP2000 and add it into 50 mL of deionized water, and treat it by ultrasound for 1 h to obtain a carbon black suspension; S3, taking the carbon black suspension prepared in step S2 and mixing it with 8 mL of the nitrogen-doped carbon dot solution prepared in step S1, stirring at room temperature for 48 h, filtering, and obtaining carbon black adsorbed with carbon dots on filter paper; S4. Using ultrasound, the carbon black adsorbed with carbon dots on the filter paper in step S3 is placed in 40 mL of deionized water to obtain a mixed solution, and 10 mL of 0.0025 mol / L zinc nitrate solution is added dropwise to the mixed solution at a dropping rate of 5 mL / min. The mixture is stirred at room temperature for 24 h, filtered to obtain a filter residue, and dried in a constant temperature oven set at 60° C. to obtain a zinc single atom-loaded Zn-NCDs / C single atom catalyst.
[0041] Reference Figure 4 , Figure 4 : The X-ray diffraction pattern of the Zn-NCDs / C single atom catalyst prepared in Example 3. The Zn-NCDs / C single atom catalyst does not show the crystal plane parameters corresponding to zinc metal, which indicates the formation and high dispersion of zinc single atoms.
[0042] Example 4 A method for preparing a metal single-atom electrocatalyst, wherein metal nickel and platinum are loaded on zero-dimensional carbon dots in the form of single atoms. The specific preparation method is as follows: S1. Take 2 g of urea and 0.5 g of citric acid and dissolve them in 20 mL of deionized water. Mix them evenly and place them in a polytetrafluoroethylene reactor. Set the reaction temperature of the polytetrafluoroethylene reactor to 180 ° C and the reaction time to 12 h. After the reaction is completed, cool the obtained product to room temperature and filter it to remove insoluble impurities to obtain an orange-yellow nitrogen-doped carbon dot solution. S2, take 40 mg of conductive carbon black BP2000 and add it into 50 mL of deionized water, and treat it by ultrasonic for 2 h to obtain a carbon black suspension; S3, taking the carbon black suspension prepared in step S2 and mixing it with 10 mL of the nitrogen-doped carbon dot solution prepared in step S1, stirring at room temperature for 48 h, filtering, and obtaining carbon black adsorbed with carbon dots on filter paper; S4. The carbon black adsorbed with carbon dots on the filter paper in step S3 is placed in 40 mL of deionized water by ultrasound to obtain a mixed solution, and a mixed solution of 5 mL of 0.0025 mol / L nickel nitrate and 5 mL of 0.0025 mol / L chloroplatinic acid is added dropwise to the mixed solution at a dropping rate of 10 mL / min. The mixture is stirred at room temperature for 24 h, filtered to obtain a filter residue, and dried in a constant temperature oven set at 60° C. to obtain a Ni, Pt-NCDs / C single atom catalyst loaded with nickel and platinum bimetallic single atoms.
[0043] Reference Figure 4 , Figure 4 The X-ray diffraction patterns of the Ni, Pt-NCDs / C single atom catalysts, conductive carbon black and commercial palladium-carbon catalysts prepared in Example 4 are shown. The peak shape of the Ni, Pt-NCDs / C single atom catalysts is similar to that of the conductive carbon black, and the crystal plane parameters corresponding to nickel and platinum metals do not appear, indicating the formation and high dispersion of nickel and platinum single atoms.
[0044] Reference Figure 5 , Figure 5 The Pt L-edge X-ray absorption near-edge structure spectrum of the Ni,Pt-NCDs / C single-atom catalyst prepared in Example 4 shows that the coordination environment around the platinum atom is mainly platinum-chlorine coordination and platinum-nitrogen coordination, that is, platinum-chlorine bonds and platinum-nitrogen bonds are formed, and no metal bonds such as platinum-platinum bonds and platinum-nickel bonds appear, further proving the formation of platinum single atoms and their loading on carbon dots and remaining independent of each other.
[0045] Example 5 A method for preparing a metal single-atom electrocatalyst, wherein metal cobalt, palladium, and platinum are loaded on zero-dimensional carbon dots in the form of single atoms. The specific preparation method is as follows: S1. Take 2 g of urea and 0.5 g of citric acid and dissolve them in 20 mL of deionized water. Mix them evenly and place them in a polytetrafluoroethylene reactor. Set the reaction temperature of the polytetrafluoroethylene reactor to 220 °C and the reaction time to 8 h. After the reaction is completed, cool the obtained product to room temperature and filter it to remove insoluble impurities to obtain an orange-yellow nitrogen-doped carbon dot solution. S2, take 40 mg of conductive carbon black BP2000 and add it into 50 mL of deionized water, and treat it by ultrasound for 1 h to obtain a carbon black suspension; S3, taking the carbon black suspension prepared in step S2 and mixing it with 10 mL of the nitrogen-doped carbon dot solution prepared in step S1, stirring at room temperature for 48 h, filtering, and obtaining carbon black adsorbed with carbon dots on filter paper; S4. Use ultrasound to place the carbon black adsorbed on the filter paper in step S3 in 40 mL of deionized water to obtain a mixed solution, and add 5 mL of 0.0025 mol / L cobalt nitrate, 5 mL of 0.0025 mol / L chloroplatinic acid and 5 mL of 0.0025 mol / L palladium chloride to the mixed solution, maintain the dropping speed of 5 mL / min, stir at room temperature for 24 hours, filter to obtain a filter residue, and dry the filter residue in a constant temperature oven set at 60°C to obtain a Co, Pd, Pt-NCDs / C single atom catalyst loaded with cobalt, palladium and platinum metal single atoms.
[0046] Reference Figure 4 , Figure 4 The X-ray diffraction patterns of the Co, Pd, Pt-NCDs / C single atom catalysts, conductive carbon black and commercial palladium-carbon catalysts prepared in Example 5 show that the peak shape of the Co, Pd, Pt-NCDs / C single atom catalysts is similar to that of the conductive carbon black, and the crystal plane parameters corresponding to cobalt, palladium and platinum metals do not appear, indicating the formation and high dispersion of cobalt, palladium and platinum single atoms.
[0047] Reference Figure 6 , Figure 6 This is a spherical aberration electron microscope image of the Co, Pd, Pt-NCDs / C single atom catalyst prepared in Example 5. In the spherical aberration electron microscope, when the electron beam passes through the sample, atoms with higher atomic numbers scatter electrons more strongly, causing more electrons to be scattered to high angles, thereby forming brighter areas in the image. That is, the isolated bright spots in the image are cobalt, palladium, and platinum with higher atomic numbers (the bright spots marked with gray circles in the image are some metal single atoms on the carrier), which are uniformly dispersed on the carbon carrier, proving the formation of cobalt, palladium, and platinum metal single atoms.
[0048] Comparative Example 1 A method for preparing a metal cluster electrocatalyst, wherein metal platinum is loaded on zero-dimensional carbon dots in the form of clusters, and the specific preparation method is as follows: Compared with Example 1, step S4 is changed to use ultrasound to place the carbon black adsorbing carbon dots on the filter paper in step S3 in 40mL deionized water to obtain a mixed solution, 10 mL 0.0025 mol / L chloroplatinic acid solution is added dropwise to the mixed solution, and then 0.05mol / L sodium borohydride solution is slowly added dropwise, maintaining a dropping rate of 0.15mL / min, and the final drop volume is about 10ml. Stir at room temperature for 6h, filter to obtain a filter residue, and dry the filter residue in a constant temperature oven set to 50°C, and the remaining steps are all the same. Obtain the Pt-NCDs / C-Cluster cluster catalyst supported by platinum clusters.
[0049] The ratio of Pt atoms in the Pt-NCDs / C-Cluster cluster catalyst prepared in Comparative Example 1 was determined to be 7.9% by inductively coupled plasma atomic emission spectrometry.
[0050] Reference Figure 2 , Figure 2 The mass activity diagram of the electrochemical methanol oxidation of the Pt-NCDs / C-Cluster cluster catalyst prepared in this comparative example 1 and the commercial platinum carbon catalyst is shown in Figure 1. The Pt-NCDs / C-Cluster cluster catalyst prepared in this comparative example 1 and the commercial platinum carbon catalyst are tested for electrochemical methanol oxidation catalytic performance in an alkaline medium (1 mol / L KOH+1 mol / L CH3OH) using a classic three-electrode system. It can be seen that the mass activity of the commercial platinum carbon catalyst is 1363.11 mA / mg Pt The mass activity of the Pt-NCDs / C-Cluster catalyst obtained in this comparative example is 3167.49 mA / mg Pt , which is 2.32 times that of commercial platinum-carbon catalyst.
[0051] Reference Figure 2 , Figure 2 The mass activity of the Pt-NCDs / C single atom catalyst prepared in Example 1 (6611.73 mA / mg Pt ) is the mass activity of the Pt-NCDs / C-Cluster catalyst prepared in Comparative Example 1 (3167.49 mA / mg Pt ) is 2.09 times of that of the cluster catalyst. This indicates that the single-atom catalyst in this preparation method is superior to the cluster catalyst in terms of mass activity.
[0052] Reference Figure 3 , Figure 3The it (chronoamperometry) curve diagram of the Pt-NCDs / C-Cluster cluster catalyst and the commercial platinum carbon catalyst prepared in this comparative example 1 is shown. The Pt-NCDs / C-Cluster cluster catalyst and the commercial platinum carbon catalyst prepared in this comparative example 1 are subjected to an electrochemical stability test in an alkaline medium (1 mol / L KOH+1 mol / L CH3OH). After 5000 s of constant voltage operation, the current density of the Pt-NCDs / C-Cluster catalyst is lower than that of the commercial platinum carbon catalyst, indicating that the stability of the Pt-NCDs / C-Cluster catalyst is worse than that of the commercial platinum carbon catalyst.
[0053] Reference Figure 3 , Figure 3 In the experiment, after 5000s of constant voltage operation, the current density of the Pt-NCDs / C single atom catalyst prepared in Example 1 was higher than that of the Pt-NCDs / C-Cluster cluster catalyst. This indicates that the single atom catalyst in this preparation method is more superior in stability than the cluster catalyst.
[0054] Reference Figure 4 , Figure 4 The X-ray diffraction patterns of the Pt-NCDs / C-Cluster cluster catalyst prepared in Comparative Example 1, conductive carbon black, and commercial palladium-carbon catalyst are shown. The Pt-NCDs / C-Cluster cluster catalyst has crystal plane parameters corresponding to platinum metal, indicating that platinum exists in the form of clusters and has poorer dispersion than single-atom catalysts.
[0055] Comparative Example 2 A method for preparing a metal cluster electrocatalyst, wherein metal palladium and ruthenium are loaded on zero-dimensional carbon dots in the form of clusters. The specific preparation method is as follows: Compared with Example 4, step S4 is changed to use ultrasound to place the carbon black adsorbing carbon dots on the filter paper in step S3 in 40mL deionized water to obtain a mixed solution, 5 mL 0.0025 mol / L palladium chloride solution and 5 mL0.0025 mol / L ruthenium chloride solution are added dropwise to the mixed solution, and then 0.05mol / L sodium borohydride solution is slowly added dropwise, and the dropping speed is maintained at 0.15mL / min, and the final drop volume is about 10ml. Stir at room temperature for 12h, filter to obtain a filter residue, and dry the filter residue in a constant temperature oven set to 50°C, and the remaining steps are all the same. Obtain Pd, Ru-NCDs / C-Cluster cluster catalysts loaded with palladium and ruthenium clusters.
[0056] Reference Figure 4 , Figure 4The X-ray diffraction patterns of the Pd, Ru-NCDs / C-Cluster cluster catalysts and commercial palladium-carbon catalysts prepared in Comparative Example 2 show that the crystal plane parameters corresponding to palladium metal appear in the peak shape of the Pd, Ru-NCDs / C-Cluster cluster catalysts, but the crystal plane parameters corresponding to ruthenium metal do not appear, which indicates that the ruthenium metal has been doped into the palladium lattice or exists in an amorphous form, indicating that ruthenium and palladium form palladium-ruthenium alloy nanostructures or palladium-ruthenium clusters, and the dispersion is worse than that of single-atom catalysts.
[0057] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal single-atom electrocatalyst, characterized in that: The following steps are involved: S1, dissolving a nitrogen source and citric acid in deionized water, mixing them evenly and placing them in a reactor, cooling and filtering after the reaction is completed to obtain a nitrogen-doped carbon dot solution; S2, taking conductive carbon black and placing it in deionized water, and ultrasonically treating it for 1-2 hours to obtain a carbon black suspension; S3, mixing the nitrogen-doped carbon dot solution obtained in step S1 and the carbon black suspension obtained in step S2, stirring for 48 hours, filtering, and obtaining carbon black adsorbed with carbon dots on filter paper; S4, using ultrasound to place the carbon black adsorbed with carbon dots on the filter paper in step S3 in deionized water to obtain a mixed solution, and dropwise adding the metal precursor solution into the mixed solution, stirring, and immersing and adsorbing at room temperature for 24 hours, filtering to obtain a filter residue, and drying the filter residue at 50-60° C. to obtain a metal single-atom electrocatalyst; The metal single-atom electrocatalyst includes a carrier and an active center; The carrier is a zero-dimensional carbon dot; The active center is a metal dispersed in the form of a single atom, and the metal is loaded on a zero-dimensional carbon point.
2. The method for preparing a metal single-atom electrocatalyst according to claim 1, characterized in that: The nitrogen source in step S1 is any one of urea and ethylenediamine.
3. The method for preparing a metal single-atom electrocatalyst according to claim 1, characterized in that: In step S1, the reaction temperature of the reactor is set to 160-240° C., and the reaction time is set to 8-12 hours.
4. The method for preparing a metal single-atom electrocatalyst according to claim 1, characterized in that: In step S1, 50-100 mg of nitrogen source is dissolved in each milliliter of deionized water; In step S1, 25-50 mg of citric acid is dissolved in each milliliter of deionized water; In the step S2, 0.6-0.8 mg of conductive carbon black is dissolved per milliliter of deionized water.
5. The method for preparing a metal single-atom electrocatalyst according to claim 1, characterized in that: In step S3, the volume ratio of the nitrogen-doped carbon dot solution to the carbon black suspension is (0.09-0.2):
1.
6. The method for preparing a metal single-atom electrocatalyst according to claim 1, characterized in that: The metal in the metal precursor solution in step S4 includes any one or more of ruthenium, rhodium, palladium, osmium, iridium, platinum, rhenium, manganese, iron, cobalt, nickel, and zinc.
7. The method for preparing a metal single-atom electrocatalyst according to claim 6, characterized in that: The metal precursor in the metal precursor solution in step S4 includes one or more of ruthenium chloride, chlororhodic acid, chloropalladic acid, chloroosmic acid, chloroiridic acid, chloroplatinic acid, rhenium chloride, manganese sulfate, manganese chloride, manganese nitrate, ferric sulfate, ferric chloride, ferric nitrate, cobalt sulfate, cobalt chloride, cobalt nitrate, nickel sulfate, nickel chloride, nickel nitrate, zinc sulfate, zinc chloride, and zinc nitrate.
8. The method for preparing a metal single-atom electrocatalyst according to claim 6, characterized in that: The concentration of the metal precursor solution in step S4 is 0.0025 mol / L; The metal precursor solution in step S4 is added at a rate of 0.1-10 mL / min; In the step S4, the volume ratio of the mixed solution to the metal precursor solution is 4:(1-1.5).
Citation Information
Patent Citations
Preparation and application of single-atom iron catalysts on basis of carbon quantum dots
CN108620072A
Nitrogen-containing carbon quantum dot modified platinum-ruthenium bimetallic methanol oxidation electrocatalyst and preparation method thereof
CN115347201A
Synthesis method of ultra-high dispersion platinoid methanol oxidation electrocatalyst
CN116314884A
Metal monatomic catalyst synthesized with assistance of graphene quantum dots, preparation method and application of metal monatomic catalyst
CN116716629A
KR20250021183A